The Winnipeg and North Pacific Railway [electronic resource] : the great highway of the new North-West : the route and its advantages : the country and its resources - Morris, W. J. (Toronto : Mail, 1889)
Signed: W.J.M. [i.e. W.J. Morris]. Prospectus for a line to run from Winnipeg via Prince Albert and Lesser Slave Lake to Port Simpson on the Pacific. Cover title. Electronic reproduction. Mode of access: Internet. 44